Cross-Dressing as Ambisexual Style: Queer Twists in Virginia Woolf’s Orlando - Adèle CASSIGNEUL (E-REA)
This paper examines cross-dressing in Virginia Woolf’s Orlando. Reading the novel’s gender topsy-turviness in light of the carnivalesque 1910 Dreadnought Hoax, for which Woolf cross-dressed as an Abyssinian Prince, I explore the seductiveness of queer non-conformity. Rather than focusing on Butlerian socio-political theories on gender, I underline the existential dimension of clothes trouble. Focusing on Orlando’s love relationships and following Clotilde Leguil’s Lacanian reading of gender vacillation, I contend that Woolf’s fanciful biography pertains to Cixous’s écriture feminine as it connects sexual difference, love and writing.